The Study of Iranian EFL Learners’ Mental Lexicon through Word Association Tests - Farid Ghaemi Shahram Halimi Passand (Universitas Ahmad Dahlan, 2015)
AbstractThis study intended to peek into Iranian EFL learners’ metal lexicon through word association tests (WATs). 31 male and female EFL learners studying at Bonab and Marageh language institutes participated in this study. A WAT comprised of 8 English words adopted from Roux’s (2013) word list administered to the participants. The results analyzed and interpreted according to both WA conventional classification and Fitzpatrick’s framework. Within conventional classification (syntagmatic, paradigmatic, and clang), the results confirmed the syntagmatic to paradigmatic change hypothesis (S→P) only between intermediate and upper-intermediate levels. The results also indicated that low intermediate learners besides other conventional factors, associate words based on phonological and orthographical relations. Within Fitzpatrick’s framework, the results indicated that learners generally associate words according to meaning and position across all proficiency levels. However, at low-intermediate level the rate of meaning-based association overwhelms position-based association. Form-based association and erratic association drew the least attention of the participants respectively. Finally, pedagogical implication of this study along with further research idea is discussed.Key words: conventional classification, Fitzpatrick’s framework, mental lexicon, word association test